PENGASUHAN KELUARGA ISLAMI DALAM MENANGANI ANAK AUTIS - Asna Asna (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2018)
Gennerally, parenting methods for children with special needs (autism) are different. This research portrays such phenomenon. The statement of problems are parenting methods used in dealing with autistic children, and their efforts which have been applied. The writer conducts this study in Tempeh Tengah, Lumajang. This study employs a qualitative descriptive method with a grounded theory approach. Data collection techniques apply in-depth interview, observation, and documentation. The conclusion are, first, the form of parenting carried out by parents is democratic method. Second, the efforts of parents in dealing with their autistic children employs behavioral therapy, drug therapy, Special School (SLB), and behavior modification therapy.